Integrating Spiritual Values, Digital Transformation, and Legal Protection in Pesantren-Based Entrepreneurship: A TCCM-Based Systematic Review: asdasd - Muhammad Anas; Umratul Khasanah; Nur Asnawi; Nuur Halimatus Sa’adiah Masrukhin (Department of Sharia Economics Faculty of Islamic Economics and Business, Universitas Islam Syarifuddin Lumajang, Indonesia, 2025)
In Indonesia, pesantren are evolving from being solely religious institutions to hybrid socio-economic institutions. These transformations stem from the assimilation of Islamic Digital entrepreneurial values and governance. However, the synergy of the facets in the candidate documents remains under-theorized and unchronicled. This research applies a Systematic Literature Review (SLR) methodology through the TCCM (Theory, Context, Characteristics, Methodology) Framework to weave together 78 peer-reviewed documents published between 2010 and 2025. The four key development pathways were distilled from bibliometric and content analyses and are as follows: the digitization of entrepreneurial waqf frameworks enhances operational efficiencies and scaling; waqf as a productive socio-economic capital; trust and moral legitimacy are obtained through Islamic business ethics; and the access to and the challenges of intellectual property are hindering institutional scale. This Study stands out in the body of available conceptual and analytical works, given that the majority of extant literature provides a striated holistic synthesis. In response, the research proposes a hybrid co-creation framework that integrates Islamic Digital entrepreneurship values and governance. This framework aims to foster socio-economic inclusivity through the collaboration of Digital MSMEs and pesantren. This work combines Islamic values of spirituality with the digital transformation and the protective legal system into a singular theoretical construct designed to reinforce entrepreneurship grounded in pesantren values, and it develops the theory by suggesting a hybrid co-creation model for its implementation.